Monaural conductive hearing loss alters the expression of the GluA3 AMPA and GlyRα1 subunits in bushy and fusiform cells of the cochlear nucleus - Wang, Hongning (2011)
The impact of conductive hearing loss (CHL), the second most common form of hearing loss, on neuronal plasticity in the central auditory pathway is unknown. After short-term (1 day) monaural earplugging, the GluA3 subunits of the AMPA receptor (AMPAR) are upregulated at auditory nerve synapses on the projection neurons of the cochlear nucleus; glycine receptor α1 (GlyRα1) subunits are downregulated at inhibitory synapses in the same neuronal population. These data suggest that CHL affects receptor trafficking at synapses. We examined the impact of 7 days of CHL on the general expression of excitatory and inhibitory receptors by quantitative biochemistry and immunohistochemistry, using specific antibodies to detect AMPAR subunits (GluA1, GluA2, GluA2/3, and GluA4), GlyRα1, and the GABA(A) receptor subunit β2/3. Following monaural earplugging and an elevation of the hearing threshold by approximately 35 dB, the immunolabeling of the antibody for the GluA2/3 subunits but not the GluA2 subunit increased on bushy cells (BCs) and fusiform cells (FCs) of the ipsilateral ventral and dorsal cochlear nuclei. These same cell types showed a downregulation of the GlyRα1 subunit. Similar results were observed in the contralateral nuclei. The expression levels of GABA(A) β2/3 were unchanged. These findings suggest that, following longer periods of monaural conductive hearing loss, the synthesis and subsequent composition of specific glutamate and glycine receptors in projection neurons and their synapses are altered; these changes may contribute to abnormal auditory processing.